An eminently humanitarian mission? Operation Acolhida and the militarized management at Venezuelan migrant shelters in Boa Vista-RR - Vasconcelos, Iana dos Santos (2022)
In 2018, the Brazilian government called the armed forces to manage shelters and control the increasing flow of Venezuelan migrants on the northern border, state of Roraima. Justified as a humanitarian mission, the Operation Acolhida, based in Boa Vista, reveals the paradoxes of a double commitment between welcoming and maintaining order. On the one hand, the military organize the shelters and distribute food and donations, and on the other, they follow protocols of surveillance and control over bodies and documents. Based on field research, with visits to militarized shelters, the article addresses: the policies circumscribing the new practices; the criteria legitimating military intervention in the management of migrant reception; the criticisms of the civil society; and some implications of this process for migratory policies in Brazil.